2018
DOI: 10.1002/2017ef000738
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Land and People Exposed to Sea‐Level Rise with No Mitigation and 1.5°C and 2.0°C Rise in Global Temperatures to Year 2300

Abstract: We use multiple synthetic mitigation sea‐level scenarios, together with a non‐mitigation sea‐level scenario from the Warming Acidification and Sea‐level Projector model. We find sea‐level rise (SLR) continues to accelerate post‐2100 for all but the most aggressive mitigation scenarios indicative of 1.5°C and 2.0°C. Using the Dynamic Interactive Vulnerability Assessment modeling framework, we project land and population exposed in the 1 in 100 year coastal flood plain under SLR and population change. In 2000, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 44 publications
0
74
0
Order By: Relevance
“…However, as the world moves closer to the year 2100, it is essential to understand SLR and the impacts of rising sea levels on longer time scales (Brown et al, 2018;P. However, as the world moves closer to the year 2100, it is essential to understand SLR and the impacts of rising sea levels on longer time scales (Brown et al, 2018;P.…”
Section: Earth's Futurementioning
confidence: 99%
See 3 more Smart Citations
“…However, as the world moves closer to the year 2100, it is essential to understand SLR and the impacts of rising sea levels on longer time scales (Brown et al, 2018;P. However, as the world moves closer to the year 2100, it is essential to understand SLR and the impacts of rising sea levels on longer time scales (Brown et al, 2018;P.…”
Section: Earth's Futurementioning
confidence: 99%
“…However, as the world moves closer to the year 2100, it is essential to understand SLR and the impacts of rising sea levels on longer time scales (Brown et al, 2018;P. A few recent studies have sought to project SLR for 2300, with median estimates of global-mean SLR ranging from 1.00 m under RCP2.6 to 11.69 m under RCP8.5 (Brown et al, 2018;Kopp et al, 2014Kopp et al, , 2017Schaeffer et al, 2012), while studies looking at multimillennial sea level commitments have suggested over 20 m of future global-mean SLR for emission scenarios similar to RCP4.5 (P. U. A few recent studies have sought to project SLR for 2300, with median estimates of global-mean SLR ranging from 1.00 m under RCP2.6 to 11.69 m under RCP8.5 (Brown et al, 2018;Kopp et al, 2014Kopp et al, , 2017Schaeffer et al, 2012), while studies looking at multimillennial sea level commitments have suggested over 20 m of future global-mean SLR for emission scenarios similar to RCP4.5 (P. U.…”
Section: Earth's Futurementioning
confidence: 99%
See 2 more Smart Citations
“…This scenario framework is made up of climate scenarios -Representative Concentration Pathways, RCPs (van Vuuren et al, 2011) -and socioeconomic scenarios -Shared Socioeconomic Pathways, SSPs -combined together into a scenario matrix . This framework (hereafter referred as SSP*RCP framework) is being increasingly used in IAV studies to explore future population exposure -under socioeconomic and climatic uncertainty -to a wide range of climate-related risks such as extreme heat (e.g., Jones et al, 2018, Rohat et al, 2019, inland and coastal flooding (e.g., Alfieri et al, 2015, Brown et al, 2018, fire risk (Knorr et al, 2016), air pollution (Chowdhury et al, 2018), and food security (e.g., Hasegawa et al, 2014). The SSP*RCP framework has been applied to some VBD-related studies (e.g., Monaghan et al 2016.…”
Section: Introductionmentioning
confidence: 99%